Acute localized exanthematous pustulosis of the leg: A case report - Wen Shuo Tiong; Sean Leong; Wei‐Sheng Chong (Wiley, 2023)
Abstract We report a case of an unusually located site of acute localized exanthematous pustulosis in the right lower limb of a patient treated with beta‐lactams which resolved upon cessation. This case report highlights the need for vigilance as well as an index of suspicion for atypical presentations.